2014
DOI: 10.4172/2157-7145.1000241
|View full text |Cite
|
Sign up to set email alerts
|

Scope of X-Chromosomal MiniSTRs: Current Developments

Abstract: The experience of using autosomal short-length amplicon STRs or miniSTRs in profiling of degraded DNA and mass disaster victims is extended into the realm of X-chromosomal (ChrX) STR miniaturization. About half of the total X-STRs are now short-length amplicons and the focus is shifting to using the mini versions of all of them. Joint multiplexing of these loci can be used for solving complex paternity cases and association of mass disaster victims with their families. This technology may herald a new dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 84 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…Stable haplotypes of closely related X-chromosome markers have shown to be useful for kinship analysis with respect to X-STRs, particularly when examining father-daughter relationships. In cases of paternity involving close blood relatives as alternative presumed fathers and in cases of paternity deficiency, where the DNA sample of the presumed father was not available and the DNA of the paternal relative should instead be analyzed, they also have an advantage over autosomal STRs [26]. The ability of autosomal STRs to rule out alternative putative dads who are close blood relations is greatly diminished in certain paternity scenarios, and X STRs may even be more powerful than autosomal (AS) markers.…”
Section: Genetic Applicationsmentioning
confidence: 99%
“…Stable haplotypes of closely related X-chromosome markers have shown to be useful for kinship analysis with respect to X-STRs, particularly when examining father-daughter relationships. In cases of paternity involving close blood relatives as alternative presumed fathers and in cases of paternity deficiency, where the DNA sample of the presumed father was not available and the DNA of the paternal relative should instead be analyzed, they also have an advantage over autosomal STRs [26]. The ability of autosomal STRs to rule out alternative putative dads who are close blood relations is greatly diminished in certain paternity scenarios, and X STRs may even be more powerful than autosomal (AS) markers.…”
Section: Genetic Applicationsmentioning
confidence: 99%
“…5 Besides, female sex markers can be applied in forensic casework for analysis of contaminated specimens containing both male and female DNA in rape cases, and can also benefit body identification from scenes of mass disaster. 6,7…”
Section: Introductionmentioning
confidence: 99%
“…5 Besides, female sex markers can be applied in forensic casework for analysis of contaminated specimens containing both male and female DNA in rape cases, and can also benefit body identification from scenes of mass disaster. 6,7 According to Scientific Working Group on DNA Analysis Methods (SWGDAM), the paternity relationship analysis, when the X chromosome is examined, is based on comparison of alleles in all tested X-STRs between two people. When all tested X-STRs have an allele in common at each locus, it concluded that two individuals are likely to have a blood relationship.…”
Section: Introductionmentioning
confidence: 99%